PELAKSANAAN SUPERVISI KEPALA SEKOLAH SD NEGERI 11 KAMPUNG BARU - Refika, Nola; Ermansyah, Vadly; Susanti, Zelly (Graduate Program Magister Manajemen Pendidikan, 2016)
: In this qualitative study, the researchers described the implementation of supervision by the principal in State Primary School 11 Kampung Baru, Batusangkar. The data in this study were from the principal and the teachers. The result revealed that the supervision activities by the principal in State Primary School 11 Kampung Baru include 1) planning; 2) actuating; and 3) funding.Â Keywords: Supervision, Principal, State Primary School 11, Batusangkar